International Conference on Managing Business Through Web Analytics - Sedkaoui, Soraya; Khelfaoui, Mounia; Benaichouba, Rafika; Mohammed Belkebir, Khalida (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book presents the proceedings of the International Conference on Managing Business Through Web Analytics (ICMBWA 2021). The conference provides a global forum for sharing knowledge and results in theory, methodology, and applications of Web Analytics and their role in the formulation and the orientation of businesses' strategies. The aim of the conference is to provide a platform for researchers and practitioners from both academia and industry to meet and share their works in the field. Is an excellent resource for scholars, experts and industrial in the fields represented, as well as Ph.D. students seeking an entryway into current research in data analytics, Web analytics, machine learning algorithms, and their various applications within businesses. Presents the proceedings of the International Conference on Managing Business through Web Analytics (ICMBWA 2021); Provides an opportunity for academics from a range of disciplines and countries to share their research in Web Analytics; Includes a platform for industrials to redefine their innovations and applications.
Introduction -- Web data: Integration, Cleaning, Analysis, Visualization, and Security -- Web Analytics Activities and Dynamics -- Social Network Analysis and Graph Algorithms -- Web Analytics, Big Data and the Internet of Things -- Business Value Creation from Web and social media analytics -- Conclusion.
Keywords: Telecommunication; Business-Data processing; Computational intelligence; Business information services; Communications Engineering, Networks; Business Analytics; Computational Intelligence; Business Information Systems